Community Structure of the Mangrove Forest in the Tourism Area of Pariaman City, West Sumatra - Meylia Alvareza; Irma Leilani (UNIVERSITAS NEGERI PADANG, 2020)
The present study aims to determine mangrove community structure in the mangrove tourism area of Pariaman City. This study has been conducted in October to December 2019 using the purposive sampling method and belt transect in three stations. A total of 21 mangrove species, 20 genera and 19 families was identified in this area. The tree level vegetation of mangroves was dominated by Sonneratia caseolaris (INP = 140,23%). The sapling level vegetation of mangroves was dominated by Dolichandrone spathacea (INP = 174,39%). The seedling and understorey level vegetation of mangroves was dominated by Acanthus ilicifolius (INP = 58%). The diversity of mangrove species in this study area is relatively low to middle (H’ = 1,574 – 2,212).